The Protection of Human Rights under the European Convention on Human Rights in Slovenia - Flander, Benjamin (European Integration Studies, 2025)
This article explores the protection of human rights under the European Convention on Human Rights (ECHR) in the Republic of Slovenia. Beginning with a brief introduction to the Council of Europe (CoE) and its key legal instrument, the ECHR, the author examines the structure of the ECHR, the rights it guarantees, the mechanisms for enforcing those rights, and its influence on both domestic legal systems and international human rights norms. The author then outlines the historical development of human rights in Slovenia, describes Slovenia’s relationship with the CoE from a human rights perspective, and reviews Slovenia’s ratification of the Convention and other CoE treaties. In the core sections, the author discusses how the ECHR’s human rights protection obligations are reflected in the Slovenian Constitution and provides an overview of the significant legislative processes that have occurred in Slovenia as a result of the implementation of the ECHR and ECtHR’s judgments. Finally, the article analyses 15 landmark cases involving Slovenia before the European Court of Human Rights (ECtHR).